Pengaruh Investasi dan Belanja Modal terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah - Esti Winarni; Abdul Aziz Ahmad; Suharno Suharno (Universitas Batanghari Jambi, 2020)
Economic growth in Central Java Province is the lowest when compared to other provinces in Java. This study aims to analyze the effect of foreign direct investments, domestic direct investment and capital expenditure on economic growth in Central Java Province. This study uses secondary data from 35 regencies / cities in Central Java Province with a period of 2013-2018. The research method uses multiple line regressions with eviews application. The results showed that foreign direct investments and capital expenditure have a positive and significant effect on economic growth and domestic direct investment have a positive and not significant effect on economic growth in Central Java Province. The implication in this study is that region governments must increase investment from abroad and use capital expenditure effective and efficient in order to encourage economic growth.